Winged bean chymotrypsin inhibitors retard growth of Helicoverpla anmigera - Telang, Manasi A.; Giri, Ashok P.; Pyati, Prashant S.; Gupta, Vidya S.; Tegeder, Mechthild; Franceschi, Vincent R. (Gene, 2009)
Two putative Kunitz-type chymotrypsin inhibitor genes (WC12 and WC15) were isolated from winged bean (Psophocarpus tetragonolobus (L.) DC). While WC12 has previously been characterized, WC15 represents a new member of the WC1 family. WC15 was exclusively expressed in winged bean seeds. Theoretical translation of both the genes resulted into polypeptides of 207 amino acids with 86% sequence similarity. The polypeptide sequences contain four half-cysteine residues and a well-conserved Leu(65)-Ser(66) reactive site, typical for chymotrypsin inhibitors. WC15 and WC12 were expressed in Pichia pastoris and the recombinant proteins were assayed against various proteinases. Both the inhibitors strongly inhibited commercially available bovine chymotrypsin. More importantly, gut proteinases of Helicoverpa armigera larvae that damage many important crop plants, were inhibited by WC12 and WC15. In addition, both proteinase inhibitors demonstrated significant reduction of growth of H. armigera larvae after feeding on inhibitor incorporated artificial diets. The inhibitory effects of WC12 and WC15 on activity of proteinases and larval growth make these proteins and their genes promising candidates for enhancing plant defense against H. armigera using transgenic plants. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Antimetabolic effect; Digestive gut proteinases; Kunitz-type proteinase inhibitor; Organ-specific mRNA expression; Psophocarpus tetragonolobus

Way toward ``dietary pesticides'': molecular investigation of insecticidal action of caffeic acid against helicoverpa armigera - Joshi, Rakesh S.; Wagh, T. P.; Sharma, N.; Mulani, Fayaj A.; Sonavane, U.; Thulasiram, H. V.; Joshi, Rakesh S.; Gupta, Vidya S.; Giri, Ashok P. (Journal of Agricultural and Food Chemistry, 2014)
Bioprospecting of natural molecules is essential to overcome serious environmental issues and pesticide resistance in insects. Here we are reporting insights into insecticidal activity of a plant natural phenol. In silico and in vitro screening of multiple molecules supported by in vivo validations suggested that caffeic acid (CA) is a potent inhibitor of Helicoverpa armigera gut proteases. Protease activity and gene expression were altered in CA-fed larvae. The structure-activity relationship of CA highlighted that all the functional groups are crucial for inhibition of protease activity. Biophysical studies and molecular dynamic simulations revealed that sequential binding of multiple CA molecules induces conformational changes in the protease(s) and thus lead to a significant decline in their activity. CA treatment significantly inhibits the insect's detoxification enzymes, thus intensifying the insecticidal effect. Our findings suggest that CA can be implicated as a potent insecticidal molecule and explored for the development of effective dietary pesticides.
Keywords: Caffeic acid; Helicoverpa armigera; insecticidal activity; protease inhibitor

Whole proteome analysis of GA(3) response at panicle stage in Grape (Vitis vinifera) CV. Thompson seedless - Maske, Smita; Upadhyay, Anuradha; Jogaiha, Satisha; Patil, Sucheta S.; Kadoo, Narendra Y.; Gupta, Vidya S. (Journal of Plant Growth Regulation, 2019)
Rachis elongation is a crucial process in producing good quality table grapes. In compact clustered grape variety like Thompson Seedless, treating the flower panicles with a mild dose of GA(3) results in loose clusters. We sprayed GA(3) on Thompson Seedless panicles immediately after emergence, and the samples were collected at 6 h and 24 h after application. Whole proteome analysis revealed significant differential expression of 530 proteins of the total 1288 expressed proteins at two time-points. GO term enrichment analysis revealed enrichment of GO terms related to translation, biosynthetic processes, and photosynthesis in GA(3)-treated samples. As the process of rachis elongation requires enhanced carbon metabolism and accumulation of sugars through the expansion of phloem area, we attribute this to the overexpression of several proteins involved in these processes. Significantly highly expressed proteins also belonged to biological processes like the generation of precursor metabolites, cellular protein metabolic processes, response to abiotic stimulus, and protein metabolic processes. This study might be the first of its kind in deciphering the contribution of a different group of proteins during rachis elongation as an early response to GA(3) application in seedless grapes. These results provide quality information on various physiological and biochemical changes occurring during early stages of rachis elongation.
Keywords: Bunch architecture; Gibberellic acid; Proteome; Rachis elongation; Vitis vinifera